Burden of arrhythmias and predictors of mortality among multiple myeloma patients with arrhythmias. (August 2022) - Balogun, Omotola; Jackson, Inimfon; Oyenuga, Mosunmoluwa; Oyenuga, Abayomi; Etuk, Aniekeme; Jackson, Nsikak
Arrhythmias are a major cardiac complication reported among patients with multiple myeloma (MM), but these have not been further characterized in this population. We explored the prevalence of arrhythmias and examined the predictors of mortality among patients with MM with arrhythmias. The National Inpatient Sample data collected between 2016 and 2018 were used to conduct retrospective analyses. Multivariable logistic regression analyses were done to examine the predictors of mortality among patients with MM with arrhythmias. 16.9% of patients with MM reported a diagnosis of any arrhythmias and 70.7% of these were atrial fibrillation. Patients aged 70 years and above had 21% lower odds (adjusted OR (AOR): 0.79; 95% CI: 0.68 to 0.92) of inpatient mortality relative to younger patients. Those in the non-Hispanic black, Hispanic, and non-Hispanic other category were 1.38 (95% CI: 1.16 to 1.64), 1.53 (95% CI: 1.19 to 1.97), and 1.69 (95% CI: 1.29 to 2.21) times more likely to die during hospitalization compared with their counterparts who were non-Hispanic whites. Relative to patients with MM who were on Medicare, those on private (AOR: 1.28; 95% CI: 1.06 to 1.54) and other insurance types (AOR: 1.78; 95% CI: 1.23 to 2.58) had higher odds of mortality. Other predictors of inpatient mortality were elective admission (AOR: 0.67; 95% CI: 0.52 to 0.85) and Charlson comorbidity indices between 5–7 (AOR: 1.23; 95% CI: 1.07 to 1.41) and ≥8 (AOR: 1.45; 95% CI: 1.21 to 1.73) compared with comorbidity indices between 0 and 4. Our study adds to the body of knowledge on the need for proper diagnosis and management of cardiac arrhythmias in patients with MM. Research is needed to further assess the time of arrhythmia diagnosis and its impact on health outcomes among patients with MM.